Why the New Deal matters - Rauchway, Eric (Yale University Press, 2021)
A look at how the New Deal fundamentally changed American life, and why it remains relevant today.
Keywords: New Deal, 1933-1939.; New Deal.; HISTORY / United States / 20th Century; New Deal, 1933-1939; 1933-1939